Indo-Us Strategic Relations in the 21st Century - Balwinder Singh (Journal of Political Studies, 2018)
The present study is to a certain extent important because of the Cold War era, IndoUS relationship has been marked by so many ups and downs. Considerably, there has been continuous enhancement in Indo-US relations in the post-Cold War era. Both the countries complete a well-built pledge to transform bilateral ties into strategic partnership during this era, mainly after 9/11. It is observed to smooth the progress of that India and the US focused on strategic, security issues, defense, maritime, energy, space, counter terrorism, trade, science and technology etc. The renovation in Indo-US strategic relationship has a vast impact on China’s security and these make corrections will have an effect on India-US-China trilateral strategic relationships in support of India. Importantly, the study has been focused on Indo-US bilateral relationship mainly in the 21st century vis-a-vis India’s security concerns at regional and global level. Thus, the study has been taking into account of the shifting global order, which is rapidly changing in the light of globalization, global terror pain in the neck and worldwide non-conventional security threats. It is also likely that let-down on the part of India to prevent delay or abandonment of the ‘‘123 civil nuclear cooperation agreement’’ has been bring substantial restrained consequences for the strategic relationship with the United States. Both the countries also decided to determine to construct nearer and qualitatively strategic ties in the 21st century. The area of convergences and divergences stuck between the two countries has been solidifying the growing model of mutual relationships. Consequently, the relevance of strategic relations makes the reading important at present time. Keeping in observation the over mentioned current development in Indo-US relations, the strategic ties process has been build a realistic impact in Indo-Pacific region and the beyond region; for that reason this subject matter has been undertaken for the research.